Periódico comunitario como propuesta de desarrollo intercultural entre los moradores del barrio de la estación del tren de Chimbacalle - Rosas Flórez, Patricio Iván (2014)
ournalism as a proposal intercultural communicative interaction spaces open community and neighborhood with the firm conviction resume and empower popular discourse and outlined in one of the neighborhoods icons growth of the city of Quito as it is Chimbacalle. The discussion outlines the scope of journalism that combines Journalistic Gender and places the actor neighborhood as a participant in the events of their community. You own trails who walks recognizes who revives the contexts and spaces. For this purpose the text raises the premise: A citizen journalism as a space of meanings and multiple relationships between the dimensions of culture own communication processes of diffusion. Premise that leads to reflection: Is communication possible alternative scenarios disruptive to the popular and everyday allowing proposals empowerment through local broadcast communication? And another: Is it possible to articulate scenarios from popular cultural and historical memory enable reconfigure in order to find the imaginary non-static processes to consolidate those that are unique and dynamic? No doubt the development proposal through the popular newspaper explained by understanding the local setting and articulate their own needs; same space as the project draws to find a site which shows the formula for an effective intercultural communication and plausible to the extent that community cultural agreements are activated by the link that makes visible the neighborhood with a product and joined by his popular revitalization project.